Creating performance benchmarks for the future elites in speed skating - Stoter, I. K.; Koning, R. H.; Visscher, C.; Elferink-Gemser, M. T. (Journal of Sports Sciences, 2019)
Sports performance benchmarks useful to select and guide future elites are limited in literature. The present study introduces a method to enable comparison between sports performance of different generations and creates performance benchmarks for the future elites in speed skating. 1500 m Season Best Times (SBT) of Dutch skaters (1043 females, 1812 males, age 13-26 years), who competed in at least six seasons between 1993 and 2013, were corrected for the prevailing world record (WR): rSBT=(SBT/WR)*100%. Regression analyses showed that the calendar year affected SBT (p<0.01), but not rSBT (p>0.05). Based on rSBT, performance groups were defined: elite (rSBT<110%), sub-elite (110%<rSBT<115%), high-competitive (115%<rSBT<120%), medium-competitive (120%<rSBT<125%) and low-competitive (rSBT>125%). Benchmarks were based on the slowest rSBT per age of the elite group. Of the total skaters performing within the elite benchmarks, the elite performance group represented <20% up to age 16 and <50% up to age 21. An out of sample group (n=299) confirmed the usability of the benchmarks. So, by correcting time-trial performance for the prevailing WR, elite performance benchmarks can be made based on multiple generations of elite skaters. The benchmarks can be used to select and guide future elite skaters from age 13-26 years